Role of gut microbiota and bacterial metabolites in mucins of colorectal cancer - Gu, Ming; Yin, Weixiang; Zhang, Jiaming; Yin, Junfeng; Tang, Xiaofei; Ling, Jie; Tang, Zhijie; Yin, Weijuan; Wang, Xiangjun; Ni, Qing; Zhu, Yunxiang; Chen, Tuo (Frontiers in Cellular and Infection Microbiology, 2023)
Colorectal cancer (CRC) is a major health burden accounting for approximately 10% of all new cancer cases worldwide. Accumulating evidences suggest that the crosstalk between the host mucins and gut microbiota is associated with the occurrence and development of CRC. Mucins secreted by goblet cells not only protect the intestinal epithelium from microorganisms and invading pathogens but also provide a habitat for commensal bacteria. Conversely, gut dysbiosis result in dysfunction of mucins allowing other commensals and their metabolites to pass through the intestinal epithelium, potentially triggering host responses and the subsequent progression of CRC. In this Review, we summarize how gut microbiota and bacterial metabolites regulate function and expression of mucin in CRC and novel treatment strategies for CRC.